Capital Structure on Dividend Policy: Is There Any Relationship? - Enow, Samuel Tabot (International Journal of Economics and Financial Issues, 2023)
Dividend pay-out policies often emanate from complex financial decisions and corporate managers do not consider dividend policies in isolation. However, some studies have indicated that capital structure significantly affects dividend pay-out and should be managed properly as it accounts for variations in dividends. The aim of this study was to investigate the relationship between capital structure and dividend pay-out. This study made use of a Kolmogorov-Smirnov and a Chi-square test. These tests are more reliable in investigating the variations and dependency between variables and are a leap from the models used in the prior literature. Using the R-square values of six published articles, the results revealed that capital structure cannot be used to explain variations in dividend pay-out as suggested by some authors. The implications of this study are that academic journals should scrutinise journal manuscripts where there are suggestions that there is a relationship between capital structure and dividend policy